The THE EFFECT OF THE APPLICATION OF THE PROBLEM BASED LEARNING (PBL) MODEL AND DIFFERENTIATIONAL LEARNING ON THE CRITICAL THINKING POWER OF ELEMENTARY SCHOOL CHILDREN: PENGARUH PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) DAN PEMBELAJARAN BERDIFERENSIASI TERHADAP DAYA BERPIKIR KRITIS ANAK SD - Usremi; Dede Margo; Ai Sutini (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2025)
The purpose of this study was to analyze the effect of the application of the Problem Based Learning (PBL) model and Differentiated Learning on improving critical reasoning in Elementary School (SD) students. PBL is an approach that focuses on solving everyday problems, while differentiated learning is learning that adapts to the needs, interests, and talents of students. The research design used was an experiment with two groups, namely the experimental group that applied PBL and the experimental group that applied differentiated learning. The instrument used to measure students' critical thinking skills before and after learning. A test that tests the ability to analyze, evaluate, and synthesize information. The results showed that the combination of PBL and differentiated learning had a great influence in stimulating students' critical reasoning. Keywords: Problem Based Learning, Differentiated Learning, critical thinking, elementary school students.